ANALISIS KINERJA KEUANGAN PT KINO INDONESIA TBK DENGAN METODE VERTIKAL-HORIZONTAL PERIODE 2018-2022 - Muhlis Muhlis; Syaiful Anwar; Zeze Zakira Hamzah; Siva Tania (Economicus : Jurnal Ekonomi dan Manajemen, 2024)
This research aims to determine the finances of PT Kino Indonesia Tbk using the vertical method and horizontal method. Results of vertical analysis of PT Kino Indonesia Tbk for the 2018-2022 period in the financial report shows that its financial performance fluctuates every year and shows quite good results seen from the value of liabilities being smaller than equity. Meanwhile, vertical analysis in the 2018-2019 profit and loss report shows a significant increase. from the profit percentage each year, but in 2020-2022 there was a decline due to the start of the coronavirus pandemic until the end of the pandemic period which caused limited business movements in various industries. Results of horizontal analysis of PT Kino Indonesia Tbk for the 2018-2022 period in the financial report show that the financial performance for 2018-2021 is quite good, judging by the percentage of total liabilities which always decreases, and total assets are greater than total liabilities, but in 2022 the results show less well, judging by the percentage increase in liabilities. short-term. Meanwhile, the horizontal analysis of the 2018-2019 profit and loss report shows quite good results assessed by the percentage of revenue that has increased, but in 2020-2022 the results are less good assessed from the percentage of revenue and profit for the current year that has decreased.